Amlodipine-induced gingival overgrowth in a child after liver transplant - Guollo, André; Vivas, Ana Paula Molina; Lopes, Rodrigo Nascimento; Porta, Gilda; Alves, Fábio Abreu (Autopsy and Case Reports, 2016)
Drug-induced gingival overgrowth (GO) has been associated with phenytoin, cyclosporine, and calcium channel blocker therapies. This study reports the case of an 11-year-old girl who was referred for evaluation of GO, which had occurred over the last 6 months. Her medical history included a liver transplant due to biliary atresia 3 years ago, immunosuppressive therapy, and hypertension, which is why she was started on a daily intake of amlodipine. The intraoral examination showed generalized GO, and the treatment consisted of a gingivectomy. Subsequently, amlodipine was replaced with captopril and oral hygiene instructions. There was no recurrence of GO after 28 months of follow-up. Although GO may be related to the chronic use of amlodipine, such an association is uncommon in pediatrics, and the treatment consists of the replacement of medication combined with a surgical approach and plaque control